Determination of Protonation Constants of Viral Inhibitor, Aurintricarboxylic Acid in SDS and CTAB Micellar Media: A Potentiometric Study - Bhargavi, K.; Shyamala, P.; Nageswara Rao, G. (Asian Journal of Chemistry, 2021)
Protonation constants of a viral inhibitor, aurintricarboxylic acid were determined using potentiometric method of data acquisition followed by chemometric modelling methods of analysis in the presence of two different kinds of micellar media, CTAB, a cationic micelle and SDS, an anionic micelle. MINIQUAD75 program was used for the determination of the plausible species and their corresponding formation constants at 303 ± 0.1 K and 0.01 M ionic strength. Five formation constants were identified corresponding to five ionizable hydrogens. Species concentration distribution diagrams were generated using Origin software. Best-fit chemical models were selected on the basis of statistical parameters like standard deviation (SD), U (sum of the squares of the residuals in mass balance equations) and chi-square test. It was found that the formation constants are lower in CTAB micellar medium while there is no significant change in the presence of SDS compared to aqueous medium.